Student Satisfaction with the Service Quality of Bank Syariah Indonesia: Importance-Performance Analysis and Customer Satisfaction Index - Anggraeni, Nahdatul; Faozan, Akhmad (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This study explores service attributes deemed important by students and assesses transactional satisfaction at Bank Syariah Indonesia (BSI). Employing quantitative research methods, a random sample of 55 students from Roudhotul Quran II Islamic Boarding School, Ciwarak, Sumbang, Banyumas, participated. The study utilized the Importance-Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methodologies. Data underwent validity and reliability tests using IBM SPSS 22. The IPA analysis identified significant attributes, including confidentiality, secure transactions, cleanliness, and unbiased service, all falling into quadrant II. The Customer Satisfaction Index (CSI) calculations revealed a satisfaction level of 81.25% during transactions, indicating contentment among customers with BSI’s service quality. Through the application of Importance-Performance Analysis (IPA), CSI, and interviews, specific areas necessitating improvement were pinpointed to enhance student satisfaction during transactions at Bank Syariah Indonesia. This research provides valuable insights into the critical factors influencing student satisfaction with BSI’s services and offers actionable recommendations for service enhancement.